The Concept of Moral Education in the Ta'limul Muta'allim Book and Its Implementation in Learning at Islamic Boarding Schools - Aziz, Abd; Saparudin, Saparudin; Zaenudin, Zaenudin; Setiawan, Yudhi (Jurnal Pendidikan Islam, 2024)
Moral education aims to develop students' cognitive abilities in order to guide their thoughts, actions, and behaviors in alignment with virtuous values that define their identities. These values are demonstrated through their interactions with God, themselves, others, and the environment, as reflections of their role as servants of Allah. The aim of this research was to provide a comprehensive analysis of the moral education concepts presented in the Ta'limul Muta'allim book, including their practical application and significance. This study employed a qualitative research approach, specifically the descriptive method. Data collecting methods were conducted using observation, interviews, and documentation procedures. The research identified various concepts of moral education in the book Ta'limul Muta'allim. These concepts include the notion of educational goals, the concept of honoring teachers, the concept of students, and the concept of civility while studying. The implementation of moral education involves incorporating the educational goal concept into subject objectives. The concept of respecting teachers encompasses the students' possession of knowledge, wara’ (piety), affection, and reverence. The concept of students entails facilitating their acquisition of knowledge, receiving affection, intending to seek Allah's blessing, demonstrating steadfastness, and respecting teachers. Furthermore, the implementation of the courtesy concept in studying knowledge necessitates that students glorify knowledge and possess wara’.